2014
DOI: 10.1002/joc.4209
|View full text |Cite
|
Sign up to set email alerts
|

Climate change effects on crop yields in Serbia and related shifts of Köppen climate zones under the SRES‐A1B and SRES‐A2

Abstract: ABSTRACT:We considered shifts in the Köppen climate zones and the corresponding impact on the crop yields in Serbia by comparing (1) the results of downscaling with the ECMWF Hamburg Atmospheric Model 5 (ECHAM5) and regional Eta Belgrade University (EBU)-Princeton Ocean Model (POM) model for the A1B and A2 scenarios over 2001-2030 and 2071-2100 and (2) the present climate simulations for the period 1961−1990. We analyzed the EBU-POM regional climate model complexity by calculating the corresponding metrics. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 50 publications
2
30
0
1
Order By: Relevance
“…The higher temperatures, more days with extreme high temperatures, and lack of precipitation lead to the simulated lower yields for maize and soybean when irrigation is not included (Jancic, 2016b;Jancic et al, 2015), and to stable and higher yields when the crop is under irrigated conditions (Jancic et al, 2015). Simulations with the CO 2 effect also gave higher yields, as in previous studies, for soybean (CECILIA, 2006;Jancic et al, 2015;Mihailović et al, 2014;Southworth et al, 2002;Wittwer, 1995) and maize (Jancic, 2016a;Mihailović et al, 2014;Wang et al, 2011). The expected increase in temperature and lack of precipitation caused higher net irrigation and lower IWUE values in the simulated maize and soybean crop productions under optimum available water conditions.…”
Section: Climate Change Impact On Yield Net Irrigation and Iwue Forsupporting
confidence: 74%
See 2 more Smart Citations
“…The higher temperatures, more days with extreme high temperatures, and lack of precipitation lead to the simulated lower yields for maize and soybean when irrigation is not included (Jancic, 2016b;Jancic et al, 2015), and to stable and higher yields when the crop is under irrigated conditions (Jancic et al, 2015). Simulations with the CO 2 effect also gave higher yields, as in previous studies, for soybean (CECILIA, 2006;Jancic et al, 2015;Mihailović et al, 2014;Southworth et al, 2002;Wittwer, 1995) and maize (Jancic, 2016a;Mihailović et al, 2014;Wang et al, 2011). The expected increase in temperature and lack of precipitation caused higher net irrigation and lower IWUE values in the simulated maize and soybean crop productions under optimum available water conditions.…”
Section: Climate Change Impact On Yield Net Irrigation and Iwue Forsupporting
confidence: 74%
“…Experimental fields were in Rimski Sancevi, located in the southern part of the Pannonian lowland (latitude 45° 20' N, longitude 19° 51' E, altitude 84 m). The experimental field location was characterized by a moderate continental climate (Mihailović et al, 2014) with an annual maximum temperature of 16.3 °C, minimum temperature of 5.9 °C, relative humidity of 74.8%, and precipitation of 576.8 mm (Rimski Sancevi station records for . The fields are the property of the Institute for Field and Vegetable Crops.…”
Section: Location and Experimental Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Lalić et al (2013) have indicated that there is an increasing trend in the observed extreme winter and summer temperatures in the Pannonian lowland. Mihailović et al (2015a) showed that it is possible to expect the shifts of Köppen climate zones in the near future; and accordingly, changes there would appear in crop yields. Besides them, other authors were using various statistical methods to analyze the spatial and temporal variability of the precipitations in Serbia in the second half of twentieth century.…”
Section: Introductionmentioning
confidence: 99%
“…The climate of Serbia can be described as mild-temperate-continental, with significant precipitation during all seasons, dry winters, and second precipitation maximum in autumn. However, the climate of Serbia is influenced by the Alps, the Mediterranean Sea, the Genoa Gulf, the Pannonian basin, the Moravian valley, the Carpathian and Rhodope mountains, the hillymountainous part with ravines and the highland plains, as well as the deep southward penetration of polar air masses, which leads to a high spatial variability (Radinović 1979;Mihailović et al 2015a). …”
Section: Introductionmentioning
confidence: 99%